2017
DOI: 10.1039/c7ta07932j
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, aqueous-electrolyte supercapacitors based on water-processable dioxythiophene polymer/carbon nanotube textile electrodes

Abstract: Water soluble-solvent resistant approach for aqueous supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 54 publications
1
40
1
Order By: Relevance
“…However, the Cs values at the scan rates of 10 and 25 mV•s -1 are slightly lower than that of 50 mV•s -1 and deviates from the usual scan rate dependency trend of the Cs (Figure 7a). This behavior has previously been observed for thin conducting polymer or metal/metal oxide based electrodes in aqueous electrolytes [48,49] and deserves to be further investigated.…”
Section: Thin Film Popd Electrodes-half Cell Performance (3-electrodesupporting
confidence: 67%
“…However, the Cs values at the scan rates of 10 and 25 mV•s -1 are slightly lower than that of 50 mV•s -1 and deviates from the usual scan rate dependency trend of the Cs (Figure 7a). This behavior has previously been observed for thin conducting polymer or metal/metal oxide based electrodes in aqueous electrolytes [48,49] and deserves to be further investigated.…”
Section: Thin Film Popd Electrodes-half Cell Performance (3-electrodesupporting
confidence: 67%
“…These materials have exceptional electrochromic properties with high contrast in the visible region and, upon reversible electrochemical doping, exhibit color‐neutral oxidized states with rapid switching times . Additionally, the broad electroactive response of the high EDOT content polymers in the ProDOT x –EDOT y (P x E y ) series has led to them being effective as capacitive materials for charge storage applications . In our previous work, we have shown that increasing the EDOT content in the repeat unit of these copolymers lowers the onset of oxidation, increases the capacitance, and lowers the optical gap ( E g ) of the resulting material.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of various aqueous electrolytes has been extensively studied with various carbon powder composite electrodes [17][18][19]. A few studies have been performed with fibrous electrodes [20] or electrospun carbon-containing electrodes [21] in aqueous electrolytes but, to our knowledge, no studies have directly electrospun fibrous electrodes of CDCs. The most fundamental studies have been performed with H 2 SO 4 -H 2 O and KOH-H 2 O electrolytes, but these electrolytes are corrosive and have a working voltage range up to 1.0 V [22][23][24].…”
Section: Introductionmentioning
confidence: 99%